The Over-Mediated World. - Tucker, Patrick (Futurist)
Media expert Michael Bugeja claims that technology creates its own value systems. Bugeja, director of the Greenlee School of Journalism and Communication at Iowa State University, is the author of Interpersonal Divide: The Search for Community in the Technological Age. He describes digital displacement, for instance, as what occurs when the demands of the real-world conflict with those of the virtual, leading to too many people giving too much attention to gadgets and ignoring reality, such as drivers interfacing with navigation computers instead of watching out for pedestrians. He is particularly worried about what the trend means for students and teachers; he says information technology is being used to entertain members of the “the Facebook Generation,” who text-message in classes, talk on their cell phones during labs, and listen to iPods rather than guest speakers in the wireless lecture hall.